A method of 'things': a relational theory of objects as persons in lived religious practice. Issue 2 (3rd May 2020) - Whitehead, Amy
ABSTRACT: Material expressions of religion are some of the most visible ways in which the lived realities of religions can be examined and understood. Religious materiality not only mediates between a continuum of still productive dualisms that exist between 'official' and 'lived' religion, but is also capable of inspiring relational methodological approaches. Based on a small-scale study of Marian statue devotion in Spain, the article asserts that 'personhood' as an approach is an appropriate conceptual and methodological tool with which to frame theoretically, address, and approach practically the religious objects that researchers encounter in the field. Such approaches are considered here as 'relational', as lived religion is best understood through the intimate relationships and negotiations that take place not only between religious group or community members, but also between human persons and other than human persons such as religious statues. Acknowledging that researchers and the objects being researched can bring each other into varying forms of personhood carries the possibility of expanding the 'participant observer' paradigm, thus expressing lines of possibilities for understanding the volatile relational phenomena that take place in the religious 'worlds' of others.